2019
DOI: 10.5958/0974-0279.2019.00005.3
|View full text |Cite
|
Sign up to set email alerts
|

Growth and instability in agricultural productivity in Odisha

Abstract: This paper analyses growth and instability in the productivity of major crops grown across the districts of Odisha, and examines its sensitivity to weather conditions during different phases of technological change. We find that except gram, the rate of growth in yield of other crops in the state is dismal. Productivity of rice, potato, maize, groundnut, and sugarcane has not only experienced deceleration but also witnessed instability over time. In Odisha, agriculture is largely rain-dependent and yield of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Therefore, efforts should be made to improve literacy rates, marketing facilities, and the transformation of low-input agriculture to high-inputhigh-value agriculture, all of which can aid in the reduction of regional differences. Some researchers looked at the growth and instability of principal crops as well as their sensitivity to climatic factors during different stages of technological development in the state of Odisha (Senapati and Goyari, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, efforts should be made to improve literacy rates, marketing facilities, and the transformation of low-input agriculture to high-inputhigh-value agriculture, all of which can aid in the reduction of regional differences. Some researchers looked at the growth and instability of principal crops as well as their sensitivity to climatic factors during different stages of technological development in the state of Odisha (Senapati and Goyari, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It contributes about 22 percent to the state's gross domestic product and engages 62 percent of the workforce. The farm sector is plagued by low labour productivity, sluggish growth and high instability, rendering agriculture-based livelihoods unsustainable (Paltasingh, Goyari, 2013;Senapati, Goyari, 2019). Notably, landholdings in the state are small -approximately three-fourths of the total 4.87 million landholdings are of a size less than or equal to one hectare (OAS, 2018(OAS, -2019.…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted during post reform period reveals that instability in agriculture has been increasing with concomitant negative effects on farmers' vulnerability [9][10][11]. While exploring the possible reasons of agricultural instability in post reform period, it is observed that studies have identified factors like lack of irrigation facilities, lack of rural infrastructure and climatic factors are the leading determinants of instability in agriculture [9,12,13]. But still there is a need to study agricultural instability at the spatial and disaggregated level to draw more relevant policy implications.…”
Section: Introductionmentioning
confidence: 99%